Neurosurgical topography of recurrent brain glioma: surgical tactics and prognosis - Rozumenko, V. D.; Mosiychuk, S. S. (Ukrainian Neurosurgical Journal, 2009)
Surgical treatment at recurrent brain glioma remains controversial. While reoperation planning there is an important question — favorable outcome achievement, actually high quality of life providing. On the base of surgical treatment results analysis at 242 patients 4 topographical glioma variants were selected and effectiveness of repeated craniotomy at recurrent tumor growth was estimated. It was set that glioma topographical variant considers to be the significant prognostic factor for surgical tactics choice and quality of life of the patient been operated.